BOILER BERBAHAN BAKAR SAMPAH - anam, ahsonul (Jurnal Sains dan Teknologi Indonesia, 2008)
Municipal waste has high economic value if the organic and inorganic waste has been separated at the source. If organic and inorganic waste mixed, municipal waste has lower (no) value and environment harmful. There are many technologies for waste treatment i e steam generator using waste as fuel. The technology produces steam and reduces the waste significantly. The experiment of steam generation system performance has beendone with waste as fuel and kerosene as a comparator fuel. The experiment with waste fuel resulted the stable flame, odorless and the time for steam formation is faster compared to kerosene stove.